The Effect of Health Education Videos on Knowledge of Food Additives - Ria Chandra Kartika; Lisus Setyowati; Malinda Capri Nurul Satya; Yoswenita Susindra (Indonesian Health Issue, 2026)
Background: School snacks remain a public health concern because some products do not meet food safety standards and may contain unsafe food additives. Limited student knowledge regarding preservatives, colorants, sweeteners, and flavor enhancers increases the risk of unhealthy snack consumption. Purpose: This study aimed to analyze the effectiveness of animated health education videos in improving elementary school students’ knowledge of food additives. Methods: A pre-experimental design with a one-group pre-test and post-test approach was conducted among 23 fifth-grade students selected through purposive sampling at SDN Karangrejo 6 in 2025. A structured knowledge questionnaire was administered before and after the animated video intervention. Data were analyzed using the Wilcoxon signed-rank test with a significance level of 0.05. Results: The proportion of students with good knowledge increased from 43% to 61%, while the proportion in the poor knowledge category decreased from 35% to 13%. Statistical analysis showed a significant difference between pre-test and post-test scores (p = 0.004). Conclusion: Animated video media is effective in improving students’ knowledge of food additives and is recommended as an innovative school-based health education strategy to strengthen food safety literacy from an early age.